Joint Costs: Evaluation Problems and Solutions (Global Journal of Management and Business Research, 2023)
Joint production is a particular type of production process that has as its output a plurality of goods that cannot separate The production of one good also implies the production of the other goods output from the process The joint production type poses two major valuation problems the determination of the cost of the products obtained from joint production and the valuation of the inventories of these goods The difficulties arise primarily because it is impossible to objectively allocate the common costs of the production process to the various products obtained from joint production It will address these issues by analysing the hypothesis of joint costs that may occur following a block sale of tangible fixed assets at a lump sum price When this hypothesis occurs the problem arises of identifying the value of the individual
Keywords: joint costs; joint production; valuation of closing inventories of joint products; bulk purchase and sale of tangible fixed assets: valuation issues